Hope for 17 patients with chronic cluster headache: efficacy evaluation of upper cervical spinal nerve root release surgery (2020–2023) - Mao-jiang, Yang; Xian, Qiong; Hong-ying, Yang; Han-wen, Zhang; Zhi-qiang, Qiu; Li-bing, He; Uzid, Mohd; Xiao-xue, Xu; Al-Goshae, Husni Ahmed Abdullah (Frontiers in Neurology, 2025)
ObjectiveWe aimed to evaluate the effectiveness and safety of upper cervical spinal nerve root release surgery in the treatment of chronic cluster headache.MethodThis retrospective study reviewed 17 patients diagnosed with chronic cluster headache who underwent upper cervical spinal nerve root release surgery between August 2020 and March 2023. Data collected included demographic information, headache characteristics (frequency, duration, and intensity), preoperative treatment regimens, and postoperative outcomes. The surgical procedure aimed to alleviate nerve compression in the upper cervical region to improve neurological function. Patients were routinely followed postoperatively to assess the therapeutic impact through headache symptom relief assessments, including headache impact tests, pain scores, and quality of life evaluations.ResultAll 17 patients completed the surgery without severe complications. Our 6-month follow-up data demonstrated notable improvements in headache symptoms, with a significant reduction in the frequency and duration of headache episodes and alleviation of pain intensity. Specifically, the Visual Analog Scale (VAS) scores at 1 week, 1 month, 3 months, and 6 months post-surgery were (2.76 ± 1.16), (2.25 ± 0.45), (1.95 ± 0.47), and (1.75 ± 0.48), respectively. The frequency of headache episodes decreased to (1.96 ± 0.42), (1.45 ± 0.36), (0.95 ± 0.32), and (0.76 ± 0.28) times per month, respectively. The duration of each episode was reduced to (14.68 ± 4.75), (9.44 ± 3.28), (6.65 ± 2.52), and (4.55 ± 1.34) minutes, respectively. Moreover, patients reported significant enhancements in quality of life and resumed normal work and social activities.ConclusionThe findings from this case series suggest that upper cervical spinal nerve root release surgery is a safe and effective treatment for chronic cluster headache, offering substantial clinical improvements. However, due to the small sample size, further large-scale, placebo-controlled studies are essential to corroborate these results, validate the long-term efficacy and safety of the procedure, and accurately determine the contribution of the surgical intervention beyond the placebo effect.